Implementation of Work Immersion and Its Effects on the Social Development of Senior High School Graduates - Kimberline Borling; Noel lozarito; Quezveen Bleau Lagdamen; Jerick Fegarido; Adonis Besa (Indonesian Journal of Educational Research and Technology, 2023)
The study was performed to determine the actual implementation of the work immersion in Sultan Kudarat State University Laboratory High School and assessed its help in the social development of Senior High School graduates. The respondents are SHS graduates of the academic year 2018, 2019, and 2020. The result of the effectiveness of work immersion on the social development of senior high school graduates is perceived as highly effective in terms of leadership skills, self-efficacy, and communication skills. Based on the analyzed result, there was a correlation and relationship between work immersion and its effects on the social development of graduates. The result also showed that the respondents did not encounter negative issues or concerns about its implementation.